2010
DOI: 10.2217/pgs.10.96
|View full text |Cite
|
Sign up to set email alerts
|

Impact of CYP2C8 and 2C9 Polymorphisms on Coronary Artery Disease and Myocardial Infarction in the LURIC Cohort

Abstract: Overall, LURIC data confirmed that there is no major cardiovascular risk associated with CYP2C8 and CYP2C9 variants in a cardiovascular risk population of patients having undergone coronary angiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 44 publications
1
11
1
1
Order By: Relevance
“…The lack of association between CYP2C9 and risk of ischemic vascular disease in this study is in accordance with other studies [79][80][81][82]. A few studies have detected an association for different subpopulations, but these findings are solitary and in the opposite direction, and have not been replicated [80,[83][84][85][86].…”
Section: Cyp2c9 and Risk Of Ischemic Vascular Diseasesupporting
confidence: 85%
See 1 more Smart Citation
“…The lack of association between CYP2C9 and risk of ischemic vascular disease in this study is in accordance with other studies [79][80][81][82]. A few studies have detected an association for different subpopulations, but these findings are solitary and in the opposite direction, and have not been replicated [80,[83][84][85][86].…”
Section: Cyp2c9 and Risk Of Ischemic Vascular Diseasesupporting
confidence: 85%
“…However, the finding could not be confirmed in a large prospective study or in a large case-control study with enough power to exclude even minor changes of risk with 90% power [78]. The lack of association between CYP2C9 and risk of ischemic vascular disease in this study is in accordance with other studies [79][80][81][82]. A few studies have detected an association for different subpopulations, but these findings are solitary and in the opposite direction, and have not been replicated [80,[83][84][85][86].…”
Section: Cyp2c9 and Risk Of Ischemic Vascular Diseasecontrasting
confidence: 46%
“…In subjects enrolled in the Ludwigshafen Risk and Cardiovascular Health (LURIC) study, no significant differences in coronary artery disease between individuals carrying different CYP2C8 and 2C9 genotypes. When the population carrying the CYP2C9*3 allele was split according to sex, increased risk of MI was found in men and decreased risk in women [59]. The use of CYP2C9 substrates and inhibitors was associated with a significant increase in the risk of myocardial infarction especially in female harbouring a variant allele (CYP2C8*2, CYP2C9*3) [60].…”
Section: Cyp2c8 Cyp2c9 Hypertension and Cardiovascular Diseasesmentioning
confidence: 99%
“…Some evidence has indicated that the levels of sex hormones could affect the development of cardiovascular and cerebrovascular diseases [20]. Sex hormones including estrogens protect against oxidative stress and are known to be vaso protective [21][22][23].…”
mentioning
confidence: 99%